Modelling Intersectionality within Quantitative Research - Christiane Gross; Lea Goldan (sozialpolitik.ch, 2023)
In the last decades, and especially since 2010, the intersectionality paradigm is being increasingly used as theoretical framework for examining and explaining social inequalities in various areas – both with qualitative and quantitative methods. So far, there is no standard for applying intersectionality in quantitative social research. Therefore, this paper aims to present how intersectionality can be applied in quantitative research and to elaborate on and evaluate several methodological approaches in this regard. More precisely, we describe the tenets of three different quantitative approaches: multivariate linear models, conventional multilevel analysis, and multilevel analysis of individual heterogeneity and discriminatory accuracy (MIAHDA). We compare the three approaches and outline their methodological benefits and limitations.